2017
DOI: 10.1111/bph.14047
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical cardiovascular safety of pitolisant: comparing International Conference on Harmonization S7B and Comprehensive in vitro Pro‐arrhythmia Assay initiative studies

Abstract: Background and PurposeWe evaluated the concordance of results from two sets of nonclinical cardiovascular safety studies on pitolisant.Experimental ApproachNonclinical studies envisaged both in the International Conference on Harmonization (ICH) S7B guideline and Comprehensive in vitro Pro‐arrhythmia Assay (CiPA) initiative were undertaken. The CiPA initiative included in vitro ion channels, stem cell‐derived human ventricular myocytes, and in silico modelling to simulate human ventricular electrophysiology. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…These findings are in line with current Fig. 2 Significant post hoc comparisons between subgroups ("add-on group," "switched group," and "naive group" [3], but may also reflect the preference, in clinical practice, to prescribe pitolisant in patients with high cardiovascular burden, given its known negligible impact on the cardiovascular system [34]. Therefore, the high prevalence of cardiovascular comorbidities may be over-estimated in our sample.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are in line with current Fig. 2 Significant post hoc comparisons between subgroups ("add-on group," "switched group," and "naive group" [3], but may also reflect the preference, in clinical practice, to prescribe pitolisant in patients with high cardiovascular burden, given its known negligible impact on the cardiovascular system [34]. Therefore, the high prevalence of cardiovascular comorbidities may be over-estimated in our sample.…”
Section: Discussionsupporting
confidence: 84%
“…In particular, pitolisant is a potent histamine H3 receptor antagonist/inverse agonist that is approved for the treatment of narcolepsy in adults. It has also been reported to inhibit KCNH2, showing voltage-gated potassium channel activity involved in ventricular cardiac muscle cell action potential repolarization 30 . From the inferred subnetworks, we also observed that KCNH2 indirectly interacts with BRAF via the AKT serine/threonine kinase 1.…”
Section: Discussionmentioning
confidence: 97%
“…Some drugs used in the treatment of narcolepsy have shown promising results in patients with craniopharyngioma with EDS or secondary narcolepsy, such as modafinil ( 18 , 26 ), methylphenidate ( 18 ), dexamphetamine ( 29 ), and pitolisant ( 24 ). In particular, pitolisant, given its low cardiovascular risk profile, may be specifically indicated for CP patients, who have many metabolic comorbidities ( 69 ).…”
Section: Discussionmentioning
confidence: 99%